تفسیرِ قرآن میں ادب ِعربی سے استشہاد: چند نمایاں عریی تفاسیر کامطالعہ (Al-Qamar, 2020)
Islamic sciences has a long tradition of argumentation from Arabic literature in the Qurr’ānic exegeses. This article is a study of prominent Arabic commentaries in this regard. It explores that argumentation from Arabic literature in the interpretation of the Qur’ānic text started from the time of the companions of the Prophet and gradually developed. In present era, it is very common in exegetical literature. Commentators of the Quran, while interpreting Qur’ānic words and verses, frequently bring evidences from Arabic literary tradition. This trend has helped a lot in better understanding of the Quran. This tradition and its current study from the context of notable Arabic commentaries can be a rich source of guidance and inspiration for the learners of the Quran as well as its contemporary commentators.
Keywords: Qur’ānic exegeses; Arabic literature, argumentation; Arabic literature; argumentation